CUTTING TIME OF THE EXPLANTS AND PHYTOREGULATORS ABOUT THE PROPAGATION IN VITRO OF JAVA CITRONELLA - SCHERER-SALVARO, Luciani Márcia; ECHER, Márcia de Moraes; GUIMARÃES, Vandeir Francisco; DALL’OGLIO-CHAVES, Elisiane Inês; FORTES, Andréa Maria Teixeira (Scientia Agraria, 2009)
The objective of this study was to evaluate the effect of the seasonally and phytoregulators about the propagation in vitro of Java citronella. The explants were collected in each season of the year and inoculated in MS medium in addition to concentrations of IBA (0,0; 0,1; 0,2 e 0,3 mg dm-3) and BAP (0,0; 1,0; 2,0 e 3,0 mg dm-3) combined and isolated among oneself. The present study was completely randomized design. At the end of 30 days the following parameters had been evaluated: height, number of shootings, formation of callus and oxidation. The higher multiplication was obtained in explants were collected during the summer (2.87 shootings) being ideal concentration 1.73 mg dm-3 of BAP in the medium culture and absence of oxidation in explants collected in this season. The height only presented significant results in explants were collected during the winter. It had formation of callus either in explants were collected during the autumn or in the winter and in the summer. But in the explants were collected during the summer it had a concomitant increase in the number of shootings. The oxidation was higher in the explants were collected during the spring.